A contribuição epistemológica canadense para a construção da arquivística contemporânea - Tognoli, Natália Bolfarini [UNESP] (2010)
The Archival Science has its development based on practice, and rises as discipline from the publication of the first archival manuals, at the end of the nineteenth century. However, new form of document production and new information technologies introduced to the discipline by the end of the twentieth century and beginning of the twenty-first century have led the archivists to rethink the archival concepts and principles that were stated by these old manuals. In this sense, in the last 30 years Canada has been fertile ground to the discussions that surround the discipline in contemporaneity and the Canadian Archival Science has played a very important role regarding the needs presented by the new forms of document production to the archivists, rediscovering principles and (re) defining concepts, methods and criteria to the creation, maintenance and use of traditional and electronic records. It was especially by the 80’s that a new paradigm was enunciated in the area, and from it, three approaches have emerged: Integrated Archival Science, enunciated by the Québec current; Functional Archival Science or Postmodern Archival Science, enunciated by Terry Cook and; Contemporary Diplomatics, first enunciated in Italy by Paola Carucci and developed and reformulated in North America by Luciana Duranti. Nevertheless there isn’t in the archival literature a systematization of these approaches contribution to the constitution of Contemporary Archival Science. In this way, the present work identifies the role of these approaches to the epistemological construction of Archival Science, especially what is the role of Québec current, Terry Cook and Luciana Duranti in this context. In such a way, an exploratory, theoretical and documental study was carried out about the Archival Science history... (Complete abstract click electronic access below)